Recurso natural y los emprendimientos turísticos en el Balneario de Agua Dulce la Reveza del cantón Palenque de la Provincia de Los Ríos - Lozada Sotomayor, María Belén (2019)
The present investigative work is directed to analyze the feasibility of tourism ventures in the natural resource, La Reveza del Palenque freshwater spa of the Province of Los Ríos, in order to obtain, in the first instance, the problem based on the matrix of problematization and the problem was prioritized in the tree where the factors that affected as a negative factor for the resource to be developed touristic were known. The elaboration of questionnaires to apply to the population that develops in the environment of the natural resource and the authorities of the Palenque Canton was used in consideration, based on the obtained data the main activities of adventure sports were obtained and thus contribute to the economic development of the locality, providing innovative ideas of tourism ventures where the population is the main beneficiaries and responsible for the rational management of the resource and the activities of adventure sports.